2017
DOI: 10.5604/01.3001.0010.5967
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion resistance of Ni-B/Si3N4 composite layers produced by electroless method

Abstract: Purpose: The paper presents the results of investigations of Ni-B/Si3N4 composite layers produced on steel substrate by electroless method. Design/methodology/approach: Amorphous silicon nitride powder (Si3N4) with nanometric particle sizes was used as a dispersion phase for the production of composite layers. Ni-B/Si3N4 composite layers were produced in baths of varying Si3N4 powder content. For comparative purposes, the study also includes results related to a Ni-B layer. The Si3N4 powder and the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The results of Mazurek et al. studies [42] displayed that the microhardness of the hard Ni–B declines by the incorporation of Si 3 N 4 nanoparticles into the matrix. In order to understand well how SiC content affects on the hardness of coatings, knowing Orowan hardening mechanism (which claims the matrix in the composite materials carries the applied force and the reinforcing particles hinder the movement and mobility of dislocations) is not sufficient here [19,41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of Mazurek et al. studies [42] displayed that the microhardness of the hard Ni–B declines by the incorporation of Si 3 N 4 nanoparticles into the matrix. In order to understand well how SiC content affects on the hardness of coatings, knowing Orowan hardening mechanism (which claims the matrix in the composite materials carries the applied force and the reinforcing particles hinder the movement and mobility of dislocations) is not sufficient here [19,41].…”
Section: Resultsmentioning
confidence: 99%
“…Bakhit et al [41] stated that alloying with cobalt element plays a significant role in reducing the Ni coatings grain size much more than SiC nanoparticles content in the matrix and our experimental results are in good agreement with his work. The results of Mazurek et al studies [42] displayed that the microhardness of the hard Ni-B declines by the incorporation of Si 3 N 4 nanoparticles into the matrix. In order to understand well how SiC content affects on the hardness of coatings, knowing Orowan hardening mechanism (which claims the matrix in the composite materials carries the applied force and the reinforcing particles hinder the movement and mobility of dislocations) is not sufficient here [19,41].…”
Section: Morphological Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Analyzing the literature, it can be easily seen that the problems related to Si 3 N 4 and NI-P are very extensively analyzed. Mazurek et al [ 24 ] showed that Ni-B/Si 3 N 4 composite layers and Ni-B composite layers are characterized by compact structures and a good adhesion to the substrate material. The incorporation of Si 3 N 4 particles into the Ni-B layers increases the degree of surface development of the layers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overly high content of nanoparticles contributes, among others, to reducing hardness and tribological properties. Nanoparticles play a very important role in improving the properties of coatings, but only the proper selection of the dispersion phase, particle size, their content, and possible heat treatment will allow obtaining the optimal coating for given operating conditions [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%